2018
DOI: 10.1002/ejoc.201800585
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride Catalyzed Asymmetric Domino Aza‐Michael Addition/[3 + 2] Cycloaddition Reactions for the Synthesis of Spiro‐ and Bicyclic α,β,γ‐Triamino Acid Derivatives

Abstract: Angularly and peri‐fused tricyclic pyrrolidinopyrazolines are efficiently prepared by LiCl‐catalyzed domino aza‐Michael addition‐1,3‐dipolar cycloaddition reactions. The absolute stereochemistry is controlled in the aza‐Michael addition step, nonaflyl azide serves as effective diazo transfer reagent to the formed enolate and the resulting diazo dipole engages in the 1,3‐dipolar cycloaddition step. The resulting tricyclic pyrrolidinopyrazolines can be easily transformed to enantiomerically enriched nonproteinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“… A direct and efficient synthesis of these functionally dense heterocycles from simple starting materials would be empowering. , Classically, tetrahydro-pyrrolo-pyrazole heterocycles are generated through cycloaddition of a diazo species with activated maleimide derivatives. , More recently, Zard demonstrated that hydrazones with pendant alkenes can be oxidized to the corresponding diazo species, which subsequently undergoes an intramolecular cycloaddition (Scheme a) . Jahn demonstrated that a domino aza -Michael reaction can afford similar heterocycles using n -BuLi and NfN 3 . , …”
Section: Introductionmentioning
confidence: 99%
“… A direct and efficient synthesis of these functionally dense heterocycles from simple starting materials would be empowering. , Classically, tetrahydro-pyrrolo-pyrazole heterocycles are generated through cycloaddition of a diazo species with activated maleimide derivatives. , More recently, Zard demonstrated that hydrazones with pendant alkenes can be oxidized to the corresponding diazo species, which subsequently undergoes an intramolecular cycloaddition (Scheme a) . Jahn demonstrated that a domino aza -Michael reaction can afford similar heterocycles using n -BuLi and NfN 3 . , …”
Section: Introductionmentioning
confidence: 99%
“…Regarding the optimized reaction conditions (Schemes 28 and 29), it was observed that the diastereomers' yields depend on the nature of cycloalkenylmethyl amines having five-or six-membered rings and α,β-unsaturated esters bearing alkyl or aryl substituents in β-position. In Scheme 30, the proposed mechanism for forming the tetrahedral-pyrrolo-pyrazole from the reaction of cycloalkenyl amines and α,β-unsaturated esters via intermediates 61-65 was postulated [25]. Moreover, Just and others [25] reported the catalytic syntheses of fused tricyclic pyrrolidinopyrazolines via aza-Michael cycloaddition of cyclic amines 55 as well as (R)-N-benzylcycloalkenyl amines 58 with NfN 3 45; the reaction was catalyzed by lithium chloride (LiCl).…”
Section: Synthesis Of the Pyrazole Ringmentioning
confidence: 99%
“…In Scheme 30, the proposed mechanism for forming the tetrahedral-pyrrolo-pyrazole from the reaction of cycloalkenyl amines and α,β-unsaturated esters via intermediates 61-65 was postulated [25]. Moreover, Just and others [25] reported the catalytic syntheses of fused tricyclic pyrrolidinopyrazolines via aza-Michael cycloaddition of cyclic amines 55 as well as (R)-N-benzylcycloalkenyl amines 58 with NfN 3 45; the reaction was catalyzed by lithium chloride (LiCl). Diastereoselective products have been obtained in good yields (68-84%) for the tricyclic products (trans)-56a-f and (cis)-57a-f, while in the case of 5,5,5-tricyclic (trans)-59a-d and (cis)-60a-d, the yield ranged from 72 to 85%.…”
Section: Synthesis Of the Pyrazole Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic strategy for angularly and peri-fused tricyclic pyrrolidino pyrazolines. (Reproduced with permission 78. Copyright 2018, Wiley).…”
mentioning
confidence: 99%